Long-term effects of exogenous silicon on cadmium translocation and toxicity in rice ( Oryza sativa L.) - Zhang, Chaochun; Wang, Lijun; Nie, Qing; Zhang, Wenxu; Zhang, Fusuo (Environmental and experimental botany, 2008)
Most nutrient solution studies on the interactions between silicon (Si) and cadmium (Cd) are short term. Here we reported a long-term experiment in which rice ( Oryza sativa L.) was cultured for 105 days and harvested at four different growth stages to measure biomass accumulation and Cd uptake and distribution in shoots and roots. Exogenous Si increased shoot biomass by 61–238% and root biomass by 48–173% when the culture solution was free of Cd. When 2 μmol L −1 Cd was added, Si supply increased shoot and root biomass by 125–171% and by 100–106% compared to the zero-Si treatment. Increasing the Cd concentration to 4 μmol L −1 decreased the beneficial effects of Si on root and shoot biomass. Silicon supply decreased shoot Cd concentrations by 30–50% and Cd distribution ratio in shoot by 25.3–46%, compared to the treatment without Si supply. Additionally, lower Si supply or more serious Cd stress would lead to roots with bigger biomass and higher Si concentration. Energy-dispersive X-ray microanalysis showed that both Si and Cd accumulated synchronously in the border and middle of phytoliths of the shoots. We conclude that Si enhances plant growth and decreases Cd accumulation in shoots and thereby helps to lower the potential risks of food contamination.